The what, why and how of health literacy: a systematic review of literature - Muhanga, Mikidadi; Malungo, Jacob (International Journal of Health, 2017)
This paper reviews literature on the concept of health literacy. Specifically the paper reviews theoretical aspects on the concept (The What); the rationale behind health literacy and how important health literacy is towards attaining good health (The Why) plus tools and approaches towards measuring and assessing Health Literacy (The How). A documentary research method was used in collecting relevant information from sixty publications. Articles reviewed were from peer-reviewed journals, conference papers, health professional studies, research by recognized independent institutions as well as systematic and narrative reviews on the topic. The review concentrated on literature published from 1970 to 2015 as the concept was developed around 1970s, excluding publications made before 1970s and non-English language publications. It is evident that the concept of Health Literacy has evolved from a basic description of the ability to perform health related tasks that require reading and computational skills, to cover cognitive capacities related to obtaining, processing, and understanding health information, leading up to decision making. There is a great need to have this particular concept and/ or process promoted taking into consideration the purposes, importance and rationale towards health care.